A study of Tunisia’s leather and date sectors - Abdelaziz, Fatma; Ellis, Mia; Zhang, Xiaobo (International Food Policy Research Institute, 2021)
Based on field visits, structured interviews, and reviews of the literature and secondary data, we examine major challenges facing the leather and date clusters in Tunisia. The challenges vary greatly between the clusters. The leather and footwear industry faces a decline in external demand. After the global economic crisis in the late 2000s and the Arab Spring in the early 2010s, the sector lost international competitiveness. To revitalize the sector, policies should be designed to expand markets for leather and footwear. Exploring trade agreement with the US, leveling the tariff rate for intermediate goods and shoes, attracting foreign direct investment, and improving leather quality are among potential options. Implementing these policies will require coordination among different government agencies and private sector stakeholders. Besides demand challenges, lack of water treatment also is a major challenge facing tanneries across Tunisia. The international demand for Tunisian dates has been very strong. Most of the major challenges are on the supply side, such as value chain coordination, inadequate water supply, labor shortages, diseases, lack of new varieties, and limited value addition. The supply-side options include diversifying varieties and expanding into date derivative and palm waste products, promoting labor-saving mechanization and water-saving irrigation technologies, and improving coordination along the value chain.